2020
DOI: 10.5817/cp2020-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Youth cyber dating abuse: A meta-analysis of risk and protective factors

Abstract: Cyber Dating Abuse (CDA) has been identified as a prevalent and negative experience for youth, which highlights the need to identify the factors associated with the occurrence of this phenomenon. Thus, this meta-analysis aims to determine the factors associated with youth CDA perpetration and victimization, identifying which of the factors present the strongest risk and protective effects. We identified 16 studies and 17 independent samples, including a total sample of 12,760 adolescents and young adults. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 70 publications
5
31
0
10
Order By: Relevance
“…The results obtained by previous studies are heterogeneous, which makes drawing definitive conclusions difficult. Some authors found no differences in CDA among university students according to age [ 4 , 60 , 61 ]. However, other studies showed that the prevalence of CDA increases as age decreases [ 17 ], although in one report a higher likelihood of being the victim of control was seen with increasing age [ 6 , 22 ], and in another the prevalence of CDA was lower in older couples [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained by previous studies are heterogeneous, which makes drawing definitive conclusions difficult. Some authors found no differences in CDA among university students according to age [ 4 , 60 , 61 ]. However, other studies showed that the prevalence of CDA increases as age decreases [ 17 ], although in one report a higher likelihood of being the victim of control was seen with increasing age [ 6 , 22 ], and in another the prevalence of CDA was lower in older couples [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who find themselves in unhealthy relationships are also more likely to experience dating violence, which includes abusive behaviors such as physical and sexual violence, stalking, and psychological abuse in real life and in virtual settings (Mendoza & Mulford, 2018). Behavior known as cyber dating abuse (CDA) takes place via information and communications technology and includes psychological aggression, physical and verbal‐emotional abuse, and exercise of control (Borrajo, Gámez‐Guadix, & Calvete, 2015; Borrajo, Gámez‐Guadix, Pereda, 2015; Caridade & Braga, 2020; Caridade et al., 2020). CDA may also result in victims' emotional distress, low self‐esteem (Hancock et al., 2017) and higher levels of depression, anxiety, and antisocial behaviors (Brown et al., 2020; Hinduja & Patchin, 2011; Reed et al., 2017; Wolford‐Clevenger et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As for the third aim, a recent meta-analysis focused on the effect of gender on cyber dating violence in adult relationships concluded that gender was not associated with cyber victimization (Gilbar et al, 2022). The meta-analysis developed by Caridade & Braga (2020) on adolescents and young adults concluded in the same direction. However, these two works also indicated the need to further explore the role of gender.…”
Section: The Present Studymentioning
confidence: 97%